A decade of antimicrobial resistance trends in Pseudomonas aeruginosa: insights from a tertiary care hospital in Saudi Arabia (2013–2022) - Yahya Shabi; Abdullah Algarni; Ali Al bshabshe; Tarik Alazraqi; Glenn Patriquin; Abdulah OS Bawazeer; Safia Abdullah Mohammed; Sara Habbash; Ali Somily; Abdulah J. Alqahtani; Saeed M. S. Alhamhhum (Frontiers in Microbiology)
BackgroundPseudomonas aeruginosa (PA) is a significant cause of nosocomial infections, and increasing antimicrobial resistance complicates management.ObjectivesTo characterize antimicrobial susceptibility trends, we conducted a retrospective study of PA clinical isolates over 10 years (2013–2022) at a tertiary care hospital in Saudi Arabia.ResultsA total of 2,490 PA isolates were analyzed (1,452 from general wards and 1,038 from ICUs). Carbapenem resistance was observed in 40% of isolates; 37.5% were multidrug-resistant (MDR), 5.3% were extensively drug-resistant (XDR), and 3.5% met the criteria for difficult-to-treat resistance (DTR).ConclusionThis study provides an overview of PA resistance pattern trends in Saudi Arabia and emphasizes the importance of establishing an antimicrobial stewardship program.